Experimental Study for Assessment of Cutting Density Effect on Hole Cleaning Efficiency in Inclined and Horizontal Wells - Mohammed, Sahmi E; H. M. Almahdawi, Faleh (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The poor hole cleaning efficiency could causes many problems such as high torque, drag, poor hydraulics and pipe stuck. These inherent problems result in an avoidable high operation cost which this study tried to address.  In this study, the effect of cutting density on hole cleaning efficiency in deviated and horizontal wells was investigated. Experiments were conducted using 40 feet (12 m) long of flow loop made from iron and PVC. However, the test section was made from PVC with (5.1m) long and (4” ID) for outer pipe and (2” OD) inner pipe. The cutting transport ratio (CTR) was determined from weight measurements for each test. Cutting Transport Ratio has been investigated for effects of the following parameters; flow rate, cutting size and density, yield point of drilling mud, and inclination angle. Once the setup was positioned at the desired inclination, the cutting was transported for 3 minutes at a constant flow rate and yield point. The amount of cutting removed during each test was thereafter weighted to determine cutting transport ratio CTR.The results obtained from this study showed that the cutting density has a slight to moderate effect on hole cleaning efficiency. Also, there was a remarkable improvement in the cutting transport ratio annular velocity and hole inclination angle was increased. However, the yield point (Yp) was negligible at maximum values of annular velocity. Therefore, at high value of yield point the cuttings with large and medium size were transported more than small size. This case is inversed at a low value of Yp. Moreover, for all sizes the heavy cutting transport less than light cutting. Finally, the critical angle was recorded between 65o-75o. Sigma plot 12.5 program has been used to graph all figures in this paper.